Motivating non-physician health workers to reduce the behavioral risk factors of non-communicable diseases in the community: a field trial study - Mehran Asadi-Aliabadi; Seyed M. Karimi; Fariba Mirbaha-Hashemi; Arash Tehrani-Banihashemi; Leila Janani; Ebrahim Babaee; Marzieh Nojomi; Maziar Moradi-Lakeh (BMC, 2023)
Abstract Background Non-communicable diseases behavioral risk factors can be improved if effective interventions are designed considering the health system's capabilities and local resources. This study evaluated the effectiveness of interventions that aimed at increasing non-physician community health workers' motivation in reducing non-communicable diseases behavioral risk factors in the community. Methods A randomized field trial study was conducted in 32 community health centers in 4 Iranian districts after a baseline population survey on the status of NCDs of 30-70-year-old individuals (n = 1225). The interventions were performed to improve insufficient physical activity, insufficient fruit consumption, insufficient vegetable consumption, high salt intake, and tobacco use. Four intervention packages were implemented in 24 community health centers; the other 8 centers were used as control groups. The non-physician community health workers performed the interventions. The packages additively included goal-setting, evidence-based education, operational planning, and incentive payments. A second survey was conducted 1 year after the start of the interventions to identify the effects on an independent random sample of 30-70-year-old individuals (n = 1221). Difference-in-difference method was used to quantify the interventions' effects. Results The average age of participants in both surveys was about 49 years. Also, about half of the participants were female, and about 43% were illiterate or had a primary school education. The interventions had statistically significant effects only on decreasing the prevalence of insufficient physical activity. The package with all the intervention components decreased the odds of insufficient physical activity to 0.24 (95% CI, 0.08, 0.72). The package with operational planning but no performance-based financing did not change the odds of insufficient physical activity. Conclusions This study highlighted the importance of components, design, and implementation details of interventions intended to reduce NCDs behavioral risk factors. Some risk factors, such as insufficient physical activity, seem more easily modifiable with limited low-cost interventions in a one-year horizon. However, risk factors related to healthy food consumption and tobacco use need more extensive interventions. Trial registration This trial was registered on the Iranian Registry of Clinical Trials (IRCT20081205001488N2) on 3 June 2018 ( https://en.irct.ir/trial/774 ).